2019
DOI: 10.21203/rs.2.13355/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preterm Births and Associated Factors among Mothers Who Gave Birth in Axum and Adwa Town Public Hospitals, Northern Ethiopia, 2018.

Abstract: Objective: The objective of this study was to determine the prevalence and associated factors of preterm births among mothers who gave birth in Axum and Adwa public hospitals, North Ethiopia, 2018. Result: This study showed that 13.3% from the total 472 mothers gave a preterm birth. Being a rural resident (AOR=2.13,95% CI:(1.07,4.22), short inter pregnancy interval (AOR= 5.4, 95% CI: (1.32, 22.05), previous preterm birth(AOR= 3.74, 95% CI: (1.03, 16.34), Premature rupture of membrane(AOR=4.14, 95% CI: (1.92, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Subsequently, a total of 27 full-text papers were assessed for eligibility on the basis of the inclusion and exclusion criteria. Four studies were excluded due to lack of an outcome of interest or no reported outcome of interest [48], and the remaining one article was excluded due to a lack of access to the full text [49]. 23 studies [29,30,31,34,35,37,38,50,51,52,53,54,55,56,57,58,59,60,61,62] were included in the final quantitative meta-analysis to estimate pooled preterm birth (Figure 1).…”
Section: Study Identification and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Subsequently, a total of 27 full-text papers were assessed for eligibility on the basis of the inclusion and exclusion criteria. Four studies were excluded due to lack of an outcome of interest or no reported outcome of interest [48], and the remaining one article was excluded due to a lack of access to the full text [49]. 23 studies [29,30,31,34,35,37,38,50,51,52,53,54,55,56,57,58,59,60,61,62] were included in the final quantitative meta-analysis to estimate pooled preterm birth (Figure 1).…”
Section: Study Identification and Characteristics Of Included Studiesmentioning
confidence: 99%